Velocity-based resistance training monitoring: Influence of lifting straps, reference repetitions, and variable selection in resistance-trained men - Jukic, I.; Garcia-Ramos, A.; Tufano, J. J. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Using lifting straps during pulling exercises (such as deadlift) may increase absolute velocity performance. However, it remains unclear whether lifting straps could also reduce the degree of relative fatigue measured by velocity decline and maintenance in a training set.